1981
DOI: 10.2307/143706
|View full text |Cite
|
Sign up to set email alerts
|

Extended and Internal Commuting in the Transformation of the Intermetropolitan Periphery

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Clark University is collaborating with JSTOR to digitize, preserve and extend access to Economic Geography. Nonmetropolitan population growth rates currently exceed those of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Such areas may even flourish demographically, by attracting in-migrants seeking cheaper housing and/or perceived improvements in lifestyle, yet within convenient range of their urban jobs. The phenomenon of exurbanisation (Spectorsky 1955) or CRD (Russwurm 1976) is well entrenched in North America, and its social and economic bases have been fully explored in the rural literature (Patel 1980;Taaffe 1980;Fisher and Mitchelson 1981;Coppack 1988;Davies and Yeates 1991;Morrill 1992;Bryant et al 2000;Schmitt and Henry 2000;Millward 2003;Walker 2003). For both cultural and economic reasons, Nova Scotia exhibits a high degree of exurban development: land prices are extremely low, development controls are minimal and a rural ethos is still prevalent.…”
Section: The Commuting Optionmentioning
confidence: 99%
“…Such areas may even flourish demographically, by attracting in-migrants seeking cheaper housing and/or perceived improvements in lifestyle, yet within convenient range of their urban jobs. The phenomenon of exurbanisation (Spectorsky 1955) or CRD (Russwurm 1976) is well entrenched in North America, and its social and economic bases have been fully explored in the rural literature (Patel 1980;Taaffe 1980;Fisher and Mitchelson 1981;Coppack 1988;Davies and Yeates 1991;Morrill 1992;Bryant et al 2000;Schmitt and Henry 2000;Millward 2003;Walker 2003). For both cultural and economic reasons, Nova Scotia exhibits a high degree of exurban development: land prices are extremely low, development controls are minimal and a rural ethos is still prevalent.…”
Section: The Commuting Optionmentioning
confidence: 99%
“…Costs There is the interesting phenomenon that households tend to underestimate or disregard the fixed and variable costs of commuting, with the result that residences are dispersed more than expected by economists (Fisher and Mitchelson 1981a). Winger (1970), for example, observed that real total expenditures of households for new homes built farther out were actually above those paid for comparable existing housing closer in.…”
Section: Underestimation Of Fixed and Variable Commutingmentioning
confidence: 99%
“…Smaller cities located in nonmetropolitan areas have emerged as important employment nodes during a period of escalating energy costs, particularly personal transportation costs (Berry and Dahmann, 1977;Taaffe, Gauthier, and Maraffa, 1980;Fisher and Mitchelson, 1981). Since the common metropolitan pattern of residential location by income will not necessarily be replicated in this setting, more empirical research is needed before explanations derived from metropolitan areas can be applied to small city commuting.…”
Section: Aspects Of the Journey-to-work Within A Small City Laborshedmentioning
confidence: 99%